Hydromorphological assessment as a tool for river basin management: The German field survey method - Meier, Georg; Zumbroich, Thomas; Roehrig, Jackson (JNRD - Journal of Natural Resources and Development, 2013)
Physical habitat characteristics are of great importance for the ecological integrity of rivers and creeks. The assessment of these hydromorphological qualities is a fundamental component of sustainable river basin management and ecologically oriented river development.This paper describes the German field survey method for hydromorphological assessement of streams and points at its potential as a tool for river basin management. We present examples for the application of the method at different management scales: analyzing the overall hydromorphological state at the river basin scale, describing specific hydromorphological characteristics at the river reach scale and monitoring the success of restoration projects at the river segment scale.We show that the German field survey method proved to be an easy-to-apply and efficient tool for river basin management since its introduction in the year 2000. Beside the method’s potentials also several drawbacks have to be considered regarding its application in other regions of the world.
Keywords: Hydromorphology; River assessment; Restoration; Monitoring; Rur River basi